Perception of Students and the Mediating Effect of Acceptance, Interactivity and LMS on Integration of Technology in HEIs - Gyau, Yaw Odame; Semarco, Stanley Kwame Marcus (Social Education Research, 2023)
Although the phenomenon of technology is gradually being integrated into tertiary education in Ghana, students’ perceptions of adopting and adapting to learning technologies for smooth integration into academic programmes in public universities remain a concern. Based on the Constructivist and Positivist paradigms, this study adopted a quantitative approach and used purposive and quota sampling to solicit data from 1,704 level 400 students in six accredited public universities. Using a regression analysis approach, ten hypotheses were tested, and the results were analyzed with Partial Least Square-Structural Equation Modelling (PLS-SEM). The study found that students’ perceptions significantly impact the integration of technology. Indirectly, students’ Acceptance and Adjustment (AA) in using technology and Learning Management System (LMS) usage significantly mediate the relationship between students’ Perceptions (PS) and technology Integration (IG). Furthermore, students’ acceptance and adjustment in adopting technology and the use of LMS are key predictors of technology integration, whereas interactivity is a weak predictor of technology integration into academic programmes in the top public universities in Ghana.